ANALISIS KADAR KALSIUM OKSALAT (CaC2O4) PADA DAUN DAN BATANG TANAMAN BAYAM DI PASAR TRADISIONAL KOTA MAKASSAR - Ardiansah Hasin; Rachmadana Zain (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2019)
This study aims to determine the levels of calcium oxalate contained in the leaves and cloves of spinach plants and their benefits as information material for the public about the presence of calcium oxalate levels in the leaves and stems of spinach plants. This type of research is experimental with quantitative analysis that is to determine the levels of calcium oxalate on the leaves and stems of spinach plants. From the analysis of 10 samples consisting of 5 leaf samples and 5 samples of spinach leaf samples one calcium oxalate leaves 0.641%, two spinach leaf samples 0.562%, three spinach leaf samples 0.481%, four spinach leaf samples 0.722%, spinach leaf samples five 0.802% and spinach stem samples one calcium oxlat level 0.641%, two spinach stem samples 0.400%, third spinach samples 0.481%, spinach four stem samples 0.481%, spinach five stem samples 0.321%, this indicates that the highest calcium oxalate in leaf samples number five and the lowest calcium oxalate in stem samples with sample code five. So that it can be concluded that calcium oxalate levels in spinach plants are more commonly found in the leaves compared to stems and are still suitable for consumption.